(untitled) (Journal of Economic Additions, 2025)
This study aims to analyze the impact of governance mechanisms, specifically the external audit mechanism, on the quality of financial statements in organizations. The analysis is based on questionnaire data collected from a sample of 32 respondents. Appropriate statistical methods were employed to test the study’s hypotheses, including Pearson correlation and simple linear regression analysis. The results revealed a statistically significant positive relationship between the external audit mechanism and the quality of financial statements. Furthermore, it was found that the external audit mechanism has a positive and significant effect on the quality of financial disclosure. Jel Classification Codes: G34, M42, M41